The cost overruns in green building development : case study Ministry of Public Works new green building project Republic of Indonesia - Putro, Anggoro (2012)
Green building technology is a relatively new technology in Indonesia. The spirit of each party to be able to support the development of this technology is a must that was inevitable. With the worst of a world energy availability conditions then of course the green building technology can be a new hope in addressing this energy shortage. The growing of green technology today will certainly stimulate spirit of each party to be able to apply the new technology in the world of construction, especially related to the development of new building. It was a common knowledge that most people's perceptions towards green building was still struggling on expensive technology, technology that was difficult to understand and even technologies that were not suitable to be applied in Indonesia. Green building versus a conventional building was still a polemic in the development of new building in Indonesia. Most of the stakeholders still thought that if this technology was applied to the project to be implemented, then the possibility of cost overruns occurred would be even greater than the conventional one’s. Assumption arose because green building technology was still a relatively new technology, which not many people truly understand and could apply this technology in every construction phase. Through this study, the researcher was trying to answer that the cost overruns occurred in green building would not be too diverse than the cost overruns occurred in conventional building, and if it happened then all parties involved would be able to know what the material or component which can cause it happened. At the end of the study, the reader would get a fairly significant result which showing that cost overruns occurred in green building construction was much lower when compared with the cost overruns occurred in conventional building. In the end, because the uncertainties had been answered, then there would be no reason for the stakeholders not to begin the construction of new buildings with green building technology.